ROLE OF BMI AND GENETIC STUDY ON MATERNAL AGE OF MOTHERS - Dr. Shradha Suman Ghanto; Pawan Mahato (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Pregnancy outcomes are influenced by a complex interplay of factors, including maternal age, body mass index (BMI), and genetic predispositions. This study delves into the intricate relationship between these variables, aiming to unravel their impact on maternal-fetal health. This research explores how maternal age, BMI, and genetic factors intersect to influence pregnancy outcomes. The study investigates genetic markers associated with fertility, maternal age, and BMI-related traits. By understanding these relationships, the study aims to pave the way for personalized healthcare interventions. A prospective cohort study design was employed, involving pregnant women from diverse age groups and BMI categories. Anthropometric measurements were recorded, genetic analyses were conducted through advanced sequencing techniques, and detailed clinical data were collected. The study focused on identifying specific genetic markers associated with maternal age, BMI, and their combined impact on pregnancy complications. This study highlights the significance of considering maternal age, BMI, and genetic factors in prenatal care. Integrating genetic insights with BMI data allows for targeted interventions, enabling personalized healthcare approaches. By understanding the unique challenges faced by mothers of different ages and BMI categories, healthcare providers can tailor interventions, ultimately improving maternal and neonatal outcomes.